IMPLEMENTASI GERAKAN MEMUNGUT SAMPAH UNTUK MENUMBUHKAN KARAKTER GOTONG ROYONG DAN PEDULI LINGKUNGAN PADA SISWA SEKOLAH DASAR - Sari, Novia Kartika; Supriyadi, Supriyadi (STKIP Persada Khatulistiwa Sintang, 2025)
The waste-picking movement was initiated due to the lack of growth in the values of cooperation and environmental awareness within the school environment. This study aims to describe the implementation of the waste-picking movement program in fostering students’ cooperative and environmental care characters. The research employed a qualitative approach with a case study design. The subjects consisted of the principal, teachers, and students. Data were collected through in-depth interviews, non-participant observation, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which includes data condensation, data display, and conclusion drawing. The results showed that the waste-picking movement program was carried out regularly every Monday and Friday through collective cleaning activities involving all school members. The program encouraged students to pick up, sort, and recycle waste into creative works. The implementation of this program proved effective in cultivating the values of cooperation and environmental care. Teachers played crucial roles as facilitators, motivators, and consistent role models. Overall, the waste-picking movement successfully fostered student character development aligned with Pancasila values, particularly cooperation and environmental responsibility.